2008
DOI: 10.3844/ajidsp.2008.237.243
|View full text |Cite
|
Sign up to set email alerts
|

Cefepime Monotherapy is as Effective as Ceftriaxone Plus Amikacin in Pediatric Patients with Cancer and High-Risk Febrile Neutropenia: A Randomized Comparison

Abstract: Abstract:The empirical use of antibiotic therapies is widely accepted in patients with fever and neutropenia during cancer chemotherapy. The use of intravenous monotherapy with broad-spectrum antibiotics in patients with high-risk of complications is an appropriate alternative. However, few data are available in pediatric patients. We conducted a prospective, randomized, open study in patients with lymphoma or leukemia who had fever and neutropenia during chemotherapy. Patients were randomized to receive cefep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
(47 reference statements)
1
11
0
2
Order By: Relevance
“…22 It is important to report that monotherapy with cefepime and meropenem is as effective as combined therapy to treat a patient with febrile neutropenia, with the advantage of enabling the association with other nephrotoxic drugs. 23,24 Thus, at that time, the possibility of nephrotoxicity was not taken into account by the association of ATRA and cefepime (cumulative dose of 32 g). Actually, no reports were found in literature regarding the interaction between cefepime and ATRA, and this does not exclude the possibility of strengthening nephrotoxicity as a result of this interaction.…”
Section: Discussionmentioning
confidence: 99%
“…22 It is important to report that monotherapy with cefepime and meropenem is as effective as combined therapy to treat a patient with febrile neutropenia, with the advantage of enabling the association with other nephrotoxic drugs. 23,24 Thus, at that time, the possibility of nephrotoxicity was not taken into account by the association of ATRA and cefepime (cumulative dose of 32 g). Actually, no reports were found in literature regarding the interaction between cefepime and ATRA, and this does not exclude the possibility of strengthening nephrotoxicity as a result of this interaction.…”
Section: Discussionmentioning
confidence: 99%
“…22 É importante relatar que as monoterapias com cefepima e meropenem, administradas à paciente são tão efetivas quanto a terapia combinada para o tratamento de paciente com neutropenia febril e apresentam a vantagem de possibilitar a associação a outros fármacos nefrotóxicos. 23,24 Por isso, naquele momento não foi considerada a possibilidade de nefrotoxicidade pela associação de ATRA e cefepima (dose cumulativa de 32 g). Aliás, não foram encontrados relatos na literatura de interação entre cefepima e ATRA, o que não descarta a possibilidade de potencialização da nefrotoxicidade como resultado dessa interação.…”
Section: Discussionunclassified
“…[8][9][10][11][12][13][14][15][16] Furthermore, exceedingly small numbers of patients in these studies had culture-proven Gram-negative bacteremia, making comparisons between the 2 empirical treatment strategies difficult. If there is a benefit of empirical combination therapy, it is unknown whether it extends to all children or whether this approach should be reserved for particular subgroups such as severely ill patients, profoundly neutropenic patients, or patients with risk factors for multidrug-resistant organisms.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] Kumar and colleagues conducted a retrospective, propensity-matched multicenter cohort study in the adult ICU population and found that empirical combination therapy was associated with decreased 28-day mortality. This benefit was most pronounced for early generation cephalosporins but did not persist when b-lactams with broader spectrums of activity were prescribed.…”
Section: Discussionmentioning
confidence: 99%